2017
DOI: 10.2139/ssrn.3008083
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Financial Accounting Information: Evidence from the Field

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Cascino et al . () interviewed 81 professional investors and similarly found that investors view financial reports as the most valuable information source for investment decisions. Interestingly, Cascino et al .…”
Section: Related Literature and Predictionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cascino et al . () interviewed 81 professional investors and similarly found that investors view financial reports as the most valuable information source for investment decisions. Interestingly, Cascino et al .…”
Section: Related Literature and Predictionsmentioning
confidence: 98%
“…Interestingly, Cascino et al . () reported that their interviewees saw financial statements as more relevant for valuation than evaluating managerial performance. There was also evidence of a perception of greater relevance for income statement items, and for EBITDA over statutory profit.…”
Section: Related Literature and Predictionsmentioning
confidence: 99%
“…However, this should not discourage academics to engage with the objectives and QCs. Recent research has started to use experiments to explore these topics (Anderson, Brown, Hodder, & Hopkins, 2015;Cascino et al, 2017) and has also begun to employ qualitative studies to address the question of what reliability means in the preparation (and audit) of accounts (Barker & Schulte, 2017;Huikku, Mouritsen, & Silvola, 2017). It is to be hoped that the IASBwhen it will start yet another CF revision at some pointcan build on more (empirical) academic insights that are able to speak to the standard-setters' conceptual challenges.…”
Section: Discussionmentioning
confidence: 99%
“…FASB’s influence over the IASB was evidenced in the later creation of a new, joint, CF for both the IASB and FASB, by 2010 where “reliability” as a fundamental QC was replaced by “faithful representation”, while “prudence” supporting “reliability”, was eliminated altogether. On these two bodies “divorce” in 2010, direct comparability diverged, the literature on financial reporting further showing that FASB were geared towards investors with a decision-useful aim, while the IASB required governance or stewardship to be financial reporting’s underlying main aim (Cascino et al , 2017; Cascino et al , 2016). The IASB’s stewardship stance is supported by Pirveli and Zimmermann (2019), along with Gassen (2008) who “revealed the controlling-usefulness is becoming more pronounced as the valuation-usefulness of accounting information declines.”…”
Section: Literature Reviewmentioning
confidence: 99%
“…"Transparency" may be an additional criteria of decision-useful financial reporting, not as some authors have proposed, a QC in its own right (Cascino et al, 2016(Cascino et al, , 2017Nobes and Stadler, 2014); and that if the chairperson of major UK banks and professors of accounting JFRA 20,2 were to be shown the recommended QCs outlined here (Figure 3), incorporating "transparency", that it may be accepted. "Transparency" appears more in the nature of a practical consideration or "criterion", rather than an enhancing QC; and as one of the criteria, may be more readily accepted by stakeholders.…”
Section: Completeness Of the Qualitative Characteristicsmentioning
confidence: 99%